A comparative analysis of clinicopathological factors between esophageal small cell and basaloid squamous cell carcinoma. Issue 8 (February 2019) - Ishida, Hirotaka; Kasajima, Atsuko; Onodera, Yu; Konno, Takuro; Maruyama, Shota; Okamoto, Hiroshi; Sato, Chiaki; Heishi, Takahiro; Sakurai, Tadashi; Taniyama, Yusuke; Takahashi, Masanobu; Fujishima, Fumiyoshi; et al.
Abstract : Abstract: Esophageal small cell carcinoma (E-SmCC) and basaloid squamous cell carcinomas (BSCCs) are both highly aggressive malignancies, but their detailed differences in clinical behaviors have remained virtually unknown. In addition, treatment strategies of the patients with E-SmCC have not been established. 29 cases of E-SmCC and 39 with BSCC were examined in this study to clarify the clinical features and outcome of the patients with E-SmCC and to compare the findings with those of BSCC. E-SmCCs presented a more advanced status than BSCC (TNM Stage: P = .002). Esophagectomy was performed in 15 small cell carcinoma patients and 14 were treated with non-surgical/systemic therapy. The clinical outcome of the small cell carcinoma cases was significantly worse than those with BSCC ( P = .001), but results of a stage-stratified analysis revealed that the Stage I small cell carcinoma patients presented favorable prognosis (3-year survival rate 100%, n = 4). In contrast, among those with Stage II–IV, clinical outcome tended to be better in the systemic therapy group (3-year survival rate 49%, n = 13) than the surgically treated group (3-year survival rate 0%, n = 12). E-SmCC was a more aggressive neoplasm than BSCC. However, early detection could possibly improve the clinical outcome of patients with E-SmCC. Systemic therapy could also benefit the patients with advanced disease (Stage II–IV). Abstract : Supplemental Digital Content is available in the text